2009
DOI: 10.1016/j.regg.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas de la escala de satisfacción con la vida en mujeres mayores activas

Abstract: These analyses showed acceptable internal consistency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
(10 reference statements)
3
8
0
2
Order By: Relevance
“…Satisfaction with life in this Mexican sample was related to depression, limiting pain, self-reported health, financial situation, and social support, and these relations ranged from r  = 0.15 to r  = 0.29 and were all statistically significant ( P  < .01), although these correlations were modest, they confirm the results found in studies with samples from different countries [2, 4, 10, 12]. The main measure correlated with SWLS was depression symptoms (loss of self-worth, sadness, feelings of despair, feelings of hopelessness or helplessness between others) can interfere directly with the perception of satisfaction of life at the same time, previous studies have found similar results [2, 15].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Satisfaction with life in this Mexican sample was related to depression, limiting pain, self-reported health, financial situation, and social support, and these relations ranged from r  = 0.15 to r  = 0.29 and were all statistically significant ( P  < .01), although these correlations were modest, they confirm the results found in studies with samples from different countries [2, 4, 10, 12]. The main measure correlated with SWLS was depression symptoms (loss of self-worth, sadness, feelings of despair, feelings of hopelessness or helplessness between others) can interfere directly with the perception of satisfaction of life at the same time, previous studies have found similar results [2, 15].…”
Section: Discussionsupporting
confidence: 85%
“…In a study of older Spanish women who remain active, Requena Hernández and collaborators [10] found a single factor that explained 51.3% of the variance. For adults 18 to 65 years of age in Chile, Vera-Villaroel and collaborators [18] found a one-factor structure that explained 59.3% of the variance and the saturation of this factor was between 0.56 and 0.88.…”
Section: Discussionmentioning
confidence: 99%
“…The SWLS is a 5-item self-report measure of global life satisfaction [ 33 ]. The Spanish version of the SWLS has well-established psychometric properties [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…To assess satisfaction with life, the Spanish language version of the Satisfaction With Life Scale (SWLS) devised by Diener, Emmons, Larsen, and Griffin (1985) and validated by Atienza, Pons, Balaguer and García-Merita (2000) was used. The SWLS is a five-item scale which presents respondents with a series of statements regarding their global judgment of their own lives.…”
Section: Variables and Measurement Instrumentsmentioning
confidence: 99%
“…Para evaluar la satisfacción con la vida se utiliza la versión castellana, validada por Atienza, Pons, Balaguer, y García-Merita (2000) de la Satisfaction With Life Scale (SWLS), de Diener, Emmons, Larsen, y Griffin (1985). La SWLS es una escala de cinco ítems en forma de afirmaciones acerca del juicio global que cada cual hace de su propia vida, con un formato de respuesta en escala Likert de 7 grados que oscila desde 1 = completamente en desacuerdo a 7 = completamente de acuerdo.…”
Section: Variables E Instrumentos De Medidaunclassified